A systematic review of time studies to assess the impact of patient transfers on nurse workload. Issue 6 (1st April 2014) - Blay, Nicole; Duffield, Christine M; Gallagher, Robyn; Roche, Michael
Abstract : Patients in hospital are increasingly being moved between clinical units and between bedspaces; however, the impact of patient transfers and bedspace moves on nurses' workload is not known. Time studies are an established observational research method that can be used to determine the duration of time taken to perform an activity or process. This review systematically searched four databases for literature published between 2000 and 2013 for observational time study techniques and patient transfers as a nurse activity. Eleven publications from three countries were included in the review. All studies used timing techniques to explore nurse work associated with the transfer process. The review highlights the duration of time spent by nurses on certain aspects of the transfer process. However, as few studies published results from timings, the impact on nurse time is likely to be higher than indicated. Further research is recommended.